Cold Regions Engineering 2019 : proceedings of the 18th International Conference on Cold Regions Engineering and the 8th Canadian Permafrost Conference, August 18-22, 2019, Quebec City, Canada - Bilodeau, Jean-Pascal; Nadeau, Daniel F.; Fortier, Daniel; Conciatori, David (American Society of Civil Engineers, 2019)
This collection contains 79 peer-reviewed papers on the current state of knowledge of cold regions science and engineering. Topics include: properties assessment and monitoring; pavements and embankments; water, snow and ice; materials, structures, and foundations; and permafrost science and engineering. This proceedings will be of interest to both researchers and practitioners involved in cold regions engineering.
Sponsored by the Canadian Geotechnical Society (Eastern Quebec and National), the Canadian Permafrost Association, the Canadian National Committee for the International Permafrost Association, and the Cold Regions Engineering Division of ASCE.
Keywords: Civil engineering -- Cold weather conditions -- Congresses.; Frozen ground -- Congresses.; Permafrost -- Congresses.; elektronické knihy; electronic books